Breaking the Budget Rule to Rescue Economy - A. Yu. Chalova (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
A high degree of uncertainty in the future development of global and Russian economy due to the corona-virus epidemic proliferation, the global economic downfall, which followed the introduction of quarantine measures in some countries make the issue of changes in state budget policy in the Russian Federation more and more acute. Despite the seeming finance stability of the budget system of the Russian Federation characterized by the surplus federal budget during two previous years and min deficit budgets of other levels, it still depends on external factors of the economic development. Policy of the Ministry of Finance aimed at adjustment of federal budget fund use to fluctuations of global oil prices within the frames of the budget rule can form considerable reserves, but at the same time it can cause a drop in investment and consumer demand and sl ow down in economy development. This approach to developing and implementing budget policy could ruin the budget essence as an active tool of state regulation of economy, especially in current conditions. Transforming the model of obligatory balance of the federal budget and accumulating sovereign reserves in conditions of growth absence in Russian economy for the large-scale stimulation of the population and business demand require scientifically grounded approach. New economic conditions demonstrate the necessity to provide well-balanced parameters of the federal budget within the frames of the budget rule. The possibility to combine these goals depends on degree of realizing key budget risks and stability of state finance to them. The article carried out modeling of key parameters of the federal budget depending on risk defining factors and effective restrictions by the budget rule provided an opportunity to advance a hypothesis that the basis of the long-term balance of Russian federal budget is formed by a new model of state budget policy leaning on the alternative use of finance tools and acceptable easing of budget rule restrictions.